Prospects of Aloe vera and its Bioactive Compounds in Diabetes: Critical Review - Sharma, Mukesh Kumar; Chauhan, Jagat; Kumar, Mohan; Joshi, Chetan Kumar; Sharma, Sandeep; Lal, Chhagan (Journal of pure & applied microbiology : an international research journal of microbiology, 2021)
Diabetes is a significant public health issue. The global diabetes epidemic has had a tremendous impact on India, and the disease burden has increased dramatically. Diabetes is quickly increasing in prevalence, especially in Indian cities, according to data. Therefore, an ideal drug is sought that has better safety and tolerability and the most effective control of diabetes. Many effective medications come from plant sources. Natural products like onion and garlic can effectively control diabetes. In this review, we should pay attention to Aloe vera and its bioactive compounds, that with the development of traditional medicine, Aloe vera can be used to treat various diseases. Some reports have questioned the safety and efficacy of Aloe vera or its compounds, especially at different doses, and some studies have shown no side effects. In this review we also focus on benefits on human health so that Aloe vera is part of the daily diet in many countries and appears to be non-toxic, it is necessary to investigate whether aloe vera dietary supplement can be a beneficial preventive or nutritional mitigation strategy to reduce the effects of diabetes. This review focuses on Aloe vera and its biologically active compounds that play a role in the treatment or prevention of this morbid disease: diabetes, including its underlying mechanism of blood sugar lowering properties, and herbal products that have been marketed for the treatment of diabetes or the therapeutic effect of diabetes.